Stereoselective Allylation of Linear and Chiral β-Amino-α-Hydroxy Aldehydes: Total Syntheses of Tetraacetyl d-lyxo-, d-ribo-, and d-arabino-Phytosphingosines - Myeong, In-Soo; Kim, Jin-Seok; Park, Muyng-Gyu; Jeon, Hwan-Hee; Jung, Changyoung; Lee, Yong-Taek; Ham, Won-Hun (Synthesis, 2018)
The stereoselective allylations of β-amino-α-hydroxy aldehydes are described. Several Lewis acids (BF3·OEt2, SnCl4, TiCl4, ZnCl2, and MgBr2·OEt2) were utilized in the allylations. The allylation of anti-β-NHCbz-α-OTBS substrate mediated by SnCl4 afforded the syn-selective product, while its allylation mediated by BF3·OEt2 afforded the anti-selective product. The allylation of syn-β-NHCbz-α-OTBS mediated by SnCl4 afforded the anti-selective product. The mechanism involves the chelation between the amido group and aldehyde oxygen by SnCl4, and the Felkin–Anh model by BF3·OEt2. The resulting allylation products were used for the total syntheses of tetraacetyl d-lyxo-, d-ribo-, and d-arabino-phytosphingosines.